2023
DOI: 10.3389/fimmu.2023.1070679
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside Rg1 as a promising adjuvant agent for enhancing the anti-cancer functions of granulocytes inhibited by noradrenaline

Abstract: IntroductionIn recent years, numerous studies have confirmed that chronic stress is closely related to the development of cancer. Our previous research showed that high levels of stress hormones secreted in the body during chronic stress could inhibit the cancer-killing activity of granulocytes, which could further promote the development of cancer. Therefore, reversing the immunosuppressive effect of stress hormones on granulocytes is an urgent problem in clinical cancer treatment. Here, we selected noradrena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 84 publications
0
2
0
Order By: Relevance
“…Research has demonstrated that both β-patchoulene and ginsenoside have anti-tumor properties. [31][32][33] These discoveries suggests that there may be potential clinical uses for shenmai injection. By leveraging these components, it may be possible to mitigate some of the undesirable side effects of radiotherapy and chemotherapy, thus improving the granulocytopenia caused by myelosuppression.…”
Section: Discussionmentioning
confidence: 99%
“…Research has demonstrated that both β-patchoulene and ginsenoside have anti-tumor properties. [31][32][33] These discoveries suggests that there may be potential clinical uses for shenmai injection. By leveraging these components, it may be possible to mitigate some of the undesirable side effects of radiotherapy and chemotherapy, thus improving the granulocytopenia caused by myelosuppression.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, studies had confirmed the immunoprotective effect of ginsenoside Rg1 on granulocytes. Ginsenoside Rg1 can serve as an adjuvant in cancer treatment to alleviate the immunosuppressive effect on granulocytes caused by chronic stress [ [4] , [5] , [6] , [7] , [8] ]. Ginsenoside Rg1 had been successfully prepared into oral enteric-coated tablets, which had obtained the national approval number, and were widely used in clinical treatment.…”
Section: Introductionmentioning
confidence: 99%